Organic onion and garlic production - Thangasamy, A; Khade, Yogesh P; Karuppaiah, V (Indian Horticulture, 2019)
Organic farming involves the use of organic amendments, biofertilizers,biological pest control, and crop rotation while excluding synthetic pesticidesand fertilizers to enhance the quality of the produce and promoteenvironmental safety. Organic farming improves physical, chemical andbiological properties of soil and improves the quality of the produce. But, itproduces 20-40% lesser yield of onion and garlic compared to conventionalfarming. However, yield could be compensated with higher premium priceavailable in the market for organic produce. Although organic farmingshows 20.0–40.0% reduction in bulb yield compared to conventional farming,it improved physical, chemical and biochemical quality of soil and qualityof the produce. The consumption of organic foods having improvedbiochemical quality may be useful in improving human health. The reducedyield of organic farming can be compensated with a premium price availablefor the organic produce in the market.